2013
DOI: 10.1111/jam.12236
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inhibition of Aspergillus niger on sedge (Lepironia articulata ) treated with heat-cured lime oil

Abstract: Aims: This study aimed to examine heat curing effect (30-100°C) on antifungal activities of lime oil and its components (limonene, p-cymene, b-pinene and a-pinene) at concentrations ranging from 100 to 300 ll ml À1against Aspergillus niger in microbiological medium and to optimize heat curing of lime oil for efficient mould control on sedge (Lepironia articulata). Methods and Results: Broth dilution method was employed to determine lime oil minimum inhibitory concentration, which was at 90 ll ml À1 with heat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…p-Cymene does not seem to have activity against filamentous fungi; the results of a study conducted by de Lira Mota et al (2012) [ 58 ] showed that p-cymene does not possess antifungal activity against Rhizopus oryzae (MICs: >1024 µg/mL for all strains). p-Cymene also showed no antifungal activity against Aspergillus niger (MIC: >300 µL/mL) [ 59 ].…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…p-Cymene does not seem to have activity against filamentous fungi; the results of a study conducted by de Lira Mota et al (2012) [ 58 ] showed that p-cymene does not possess antifungal activity against Rhizopus oryzae (MICs: >1024 µg/mL for all strains). p-Cymene also showed no antifungal activity against Aspergillus niger (MIC: >300 µL/mL) [ 59 ].…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…Essential oils are very well known for their use to inhibit or kill molds (Bluma and Etcheverry, 2008;Matan et al, 2012Matan et al, , 2013Matan et al, , 2014. Several studies have reported the efficacy of essential oil in vapor phase against molds (Nielsen and Rios, 2000;Avila-Sosa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of mild heat (60-70°C) on the volatile composition of essential oil was reported by Matan et al (2013) and Olmedo et al (2015). Results showed an increase of some main components after thermal study.…”
Section: Optimization Of Absorbent Materials On the Growth Of Aflavusmentioning
confidence: 80%